Faktor-Faktor yang Mempengaruhi Kinerja Manajerial Pada Organisasi Perangkat Daerah di Kabupaten Boyolali - Ninda Sekar Kusuma Wijaya; Era Trianita Saputra (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
Managerial performance determines the success of an organization in achieving its goals. Managerial performance can be achieved if it is carried out according to each authority and responsibility without violating applicable rules (yogi, 2018). In the public sector, especially government, managerial performance has an important impact on the welfare of society. This research aims to analyze the significance of the influence of budget participation, organizational climate, leadership style, and organizational commitment. The type of research used in this research is quantitative research, the data source used is primary data. The boyolali regency regional government from 31 regional apparatus organizations (opd) totaling 476 people. The sample selected was echelon ii, echelon iii and echelon iv structural officials from 31 boyolali regency opds with 93 respondents. The sample was determined using a non-probability sampling technique. The data collection technique uses a questionnaire instrument which goes through the validity and reliability testing stage first. Test the regression requirements using the classic assumption test. The data analysis technique uses multiple linear regression analysis, t test, f test and coefficient of determination. Based on the results of the research that has been conducted, it can be concluded that budget participation, organizational climate, and organizational commitment have a significant effect on managerial performance, while leadership style has no effect on managerial performance